2013
DOI: 10.1614/ws-d-12-00203.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Glyphosate-Tolerant Soybean Yield Components to Dicamba Exposure

Abstract: Exposure of soybean to dicamba can result in leaf malformation and sometimes yield loss, but it is unclear how yield components are affected by exposure to low quantities of this herbicide. The objectives were to characterize soybean injury and quantify changes in seed yield and yield components of soybean plants exposed to dicamba, and determine if seed yield loss can be estimated from visual injury ratings. Nine dicamba rates (0, 0.06, 0.23, 0.57, 1.1, 2.3, 4.5, 9.1, and 22.7 g ae ha−1) were applied at three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
83
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(112 citation statements)
references
References 28 publications
16
83
0
1
Order By: Relevance
“…In contrast, ROBINSON et al (2013b) reported equivalent soybean injury for 2,4-D at rate ranging from 145 and 245g ha -1 . These results are consistent with those reported by GRIFFIN et al 2013; ROBINSON et al, (2013aROBINSON et al, ( , 2013b and SOLOMON & BRADLEY, 2014, who reported that soybean exposure to auxin herbicides drift causes significant more crop injury when applied during vegetative than reproductive stage.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…In contrast, ROBINSON et al (2013b) reported equivalent soybean injury for 2,4-D at rate ranging from 145 and 245g ha -1 . These results are consistent with those reported by GRIFFIN et al 2013; ROBINSON et al, (2013aROBINSON et al, ( , 2013b and SOLOMON & BRADLEY, 2014, who reported that soybean exposure to auxin herbicides drift causes significant more crop injury when applied during vegetative than reproductive stage.…”
Section: Resultssupporting
confidence: 92%
“…The degree of injury observed in soybean for 2,4-D and dicamba herbicides were similar to those observed in soybean (GRIFFIN et al, 2013;ROBINSON et al, 2013aROBINSON et al, , 2013bSOLOMON & BRADLEY, 2014). Soybean exhibited the greatest symptoms injury to 2,4-D between 26 and 32% for V 5 and R 2 stages at high rate, respectively ( Figure 1).…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Yield losses of greater than 18% have been reported due to 1% tank contamination with dicamba in soybean (Derksen 1989;Griffin et al 2013). Robinson et al (2013) found 10% or more yield loss in soybean when exposed to dicamba applied at 22.7 g a.e. ha −1 .…”
Section: Introductionmentioning
confidence: 99%